The Pharmacist Role in Clinical Audit at an Indian Accredited Hospital: An Interventional Study - Sah, Naresh; Ramaiah, Balakeshwa; Koneri, Raju (Indian Journal of Pharmacy Practice)
Objective: Irrational use of drugs in medical practice is a major health problem. The objective of this study was to audit the prescriptions, categorize the types of errors identified by a clinical pharmacist, improve the prescription practice along with generation of information on the core prescribing pattern and demonstrate the common therapeutic interventions that can be done in NABH accredited hospital. Methods: This prospective interventional study included 245 cases for the audit. The prescription audit was performed in accordance with manual of prescribing indicators by WHO. The therapeutic audit was conducted using hospital antibiotic policy, ISMP guidelines, standard ADRs assessment scales and databases like Stockley’s drug interaction, Micromedex, Clinirex, Medscape and Lexicomp. Results: Upon prescription audit, drugs prescribed by generic names were in 77.5% of cases. Only 5.06% of total drugs were found to be Fixed Dose Combinations (FDCs) but were used in 37.5% of cases. Injectable dosage forms were in majority (45.14%). Diseases of respiratory system (40.42 %) were found to be highest. The total numbers of prescribed drugs for all 245 cases were 2074, which is approximate equals to 8.46 ± 0.27 drugs per case. Out of 40 interventions, 15% were noncompliance to antibiotic policy, 7.5% therapeutic duplications, 22 ADRs, 5% contraindications, 7.5% dose adjustment and 5% untreated indication. Conclusion: There is still huge scope for improvement in prescribing pattern in NABH accredited hospital. The clinical pharmacist can revolutionize the face of Indian healthcare setup by working closely with medical and nursing staff with assurance of the most optimized treatment for patients.
Keywords: Therapeutic Audit; Clinical Pharmacist; Medication Error; Irrational Drug Use; Polypharmacy; Intervention.